OCCUPATIONAL CHOICE OF YOUTHS AND AGRICULTURAL DEVELOPMENT IN OVO STATE OF NIGERIA - E A Laogun (Journal of Agricultural Extension, 2015)
The study examined the factors which influence the occupational choice of youths in Oyo State of Nigeria. Information was obtained through the use of structured questionnaire. Results of data analysis indicate that 30% of respondents chose medicine as their career, 22.5% chose engineering as their future occupation, while careers in computer science came third (20%) in the occupational choice of the respondents and agriculture and teaching occupations attracted 6% and 5% respectively. Parents are more influential in assisting the youths with their occupational aspirations. Agricultural occupation is not favoured by a great majority of respondents because of lack of clear understanding as to what are involved in agricultural occupations. The paper provides different ways of educating students about career choice.